Photo-acclimatory thresholds anticipate sudden shifts in seagrass ecosystem state under reduced light conditions. (May 2022) - Marín-Guirao, L.; Bernardeau-Esteller, J.; Belando, M.D.; García-Muñoz, R.; Ramos-Segura, A.; Alcoverro, T.; Minguito-Frutos, M.; Ruiz, J.M.
Abstract: Seagrass ecosystems usually respond in a nonlinear fashion to increasing pressures and environmental changes. Feedback mechanisms operating at the ecosystem level and involving multiple interactions among the seagrass meadow, its associated community and the physical environment are known to play a major role in such nonlinear responses. Phenotypic plasticity may also be important for buffering these ecological thresholds (i.e., regime shifts) as many physiological processes show nonlinear responses to gradual environmental changes, conferring the appearance of resistance before the effects at the organism and population levels are visible. However, the potential involvement of plant plasticity in driving catastrophic shifts in seagrass ecosystems has not yet been assessed. In this study, we conducted a manipulative 6-month light-gradient experiment in the field to capture nonlinearities of the physiological and population responses of the seagrass Cymodocea nodosa to gradual light reduction. The aim was to explore if and how the photo-acclimatory responses of shaded plants are translated to the population level and, hence, to the ecosystem level. Results showed that the seagrass population was rather stable under increasing shading levels through the activation of multilevel photo-acclimative responses, which are initiated with light reduction and modulated in proportion to shading intensity. The activation of photo-physiological and metabolic compensatory responses allowed shaded plants to sustain nearly constant plant productivity (metabolic carbon balance) along a range of shading levels before losing linearity and starting to decline. The species then activated plant- and meadow-scale photo-acclimative responses and drew on its energy reserves (rhizome carbohydrates) to confer additional population resilience. However, when the integration of all these buffering mechanisms failed to counterbalance the effects of extreme light limitation, the population collapsed, giving place to a phase shift from vegetated to bare sediments with catastrophic ecosystem outcomes. Our findings evidence that ecological thresholds in seagrass ecosystems under light limitation can be explained by the role of species' compensatory responses in modulating population-level responses. The thresholds of these plastic responses anticipate the sudden loss of seagrass meadows with the potential to be used as early warning indicators signalling the imminent collapse of the ecosystem, which is of great value for the real-world management of seagrass ecosystems. Graphical abstract: Image 1 Highlights: The role of phenotypic plasticity in buffering seagrass regime shift is explored. A field light-gradient experiment captured nonlinear Cymodocea nodosa responses. Multilevel photo-acclimative responses conferred population resistance to shading. When compensatory responses failed the population collapsed at extreme shading levels. Plant response thresholds are early warning indicators of seagrass ecosystem collapse.